Faktor Pendorong Sekolah Menengah Baru di Era Zonasi: Analisis Peluang dan Tantangan di Kota Jayapura - Lazarus Ramandei; Geelvinka M. Catharine; Miracle O. Phaulhentje; Cornelicha M. Alberthine Ramandey (BADAN PENERBIT STIEPARI PRESS, 2025)
The implementation of the zoning system since 2017 has triggered significant transformation in the secondary education landscape in Jayapura City, including the emergence of new secondary schools as a response to policy changes. This study aims to analyze the factors that trigger the proliferation of new secondary schools in Jayapura City during the zoning era and identify the opportunities and challenges that accompany it. Using a qualitative approach with case study methods, this research involved in-depth interviews with 35 key informants including education providers, local government, and community representatives, as well as analysis of licensing documents and educational statistics data for the 2017-2024 period. The results showed a significant increase in the number of secondary schools in Jayapura City from 68 units in 2017 to 89 units in 2024, representing growth of 30.9%. The main factors triggering the emergence of new schools include: limited capacity of existing schools within the zoning system, profitable education business opportunities due to excess demand, demands for geographical equity in education access particularly in peripheral areas, resistance to the zoning system from upper-middle economic groups seeking quality alternatives, and diversification needs for specialized education programs. Identified opportunities include improved access to education in underserved areas, increased infrastructure investment totaling Rp 189.5 billion, and healthy competition driving educational innovation. Main challenges include quality disparities between schools, potential fragmentation of the education system, operational sustainability issues affecting 14.3% of new schools, and shortage of 546 qualified teaching staff. The research recommends the need for stricter regulations on the establishment of new schools, comprehensive accreditation systems, and integration strategies for new schools in a sustainable zoning education ecosystem that ensures equitable access to quality education.